Study of the escalating cost of living and poverty in the Caribbean : mobilising collective response at the regional level : main report (The Company TunapunaTT, 2008)
Seeks to provide some guidelines for immediate collective response at the regional level by identifying those food and non-food commodities which may be candidates for the removal or reduction of the CET, on the basis of their weight in the CPI basket and the CET which they currently attract, given that they are not significantly produced or have a close substitute in the region and have relevance to the quality of life that residents enjoy.
Keywords: COST OF LIVING